1999
DOI: 10.1159/000010159
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression in Primary, Metastatic and Recurrent Lesions of Endometrial Cancer

Abstract: Seventeen patients with endometrial cancer were studied. Tissues of primary (P) and metastatic (M) lesions were obtained from 8 patients and complete sets of P, M and Recurrent (R) lesions were obtained from 9 patients during a follow-up period of 1–10 years. Expressions of estrogen receptors, progesterone receptors, multidrug resistance protein-1, multidrug resistance-related protein, c-erbB-2, membrane-type metalloproteinase, human telomerase RNA, human telomerase reverse transcriptase RNA, E-cadherin and au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…We found that PR expression decreased significantly with increasing disease severity. This conclusion is consistent with many previous reports that loss of PR expression correlates with advanced disease [ 37 , 38 ]. Next, we investigated the mechanisms which contribute to PR loss.…”
Section: Discussionsupporting
confidence: 94%
“…We found that PR expression decreased significantly with increasing disease severity. This conclusion is consistent with many previous reports that loss of PR expression correlates with advanced disease [ 37 , 38 ]. Next, we investigated the mechanisms which contribute to PR loss.…”
Section: Discussionsupporting
confidence: 94%
“…In the current study, MT1‐MMP protein was mainly localized to neoplastic epithelial cells, as also reported in lung and gastric carincomas 24, 25. The current data support previous studies showing that endometrial tumor cells are the main producers of MT1‐MMP mRNA in endometrial carcinoma26 and that high MT1‐MMP gene expression in primary endometrial carcinoma tissue correlates with MT1‐MMP expression in metastatic lesions 27. We observed a correlation of MT1‐MMP protein expression with both increasing depth of myometrial invasion and the presence of vascular/lymphatic invasion.…”
Section: Discussionsupporting
confidence: 91%
“…During progression of endometrial cancer, the expression of PR is decreased (Arnett-Mansfield et al 2001, Fujimoto et al 1995, Fukuda et al 1998, Kumar et al 1998, Sakamoto et al 1999. Although it remains unclear whether this is a consequence of down-regulation of only one PR isotype or both, several studies suggest that relative over-expression of PRB is associated with more aggressive tumour growth.…”
Section: Introductionmentioning
confidence: 99%